Math

how would you factor 4x-x^2-3/ x-1...so that x-1 would cancel out?

could you explain step by step..plz

  1. 👍
  2. 👎
  3. 👁
  1. (4x-x^2-3)/(x-1)
    = -(x^2 - 4x + 3)/(x-1)
    = -(x-1)(x-3)/(x-1)
    = -(x-3), x not equal to 1

    1. 👍
    2. 👎
  2. Rearrange the numerator to become

    (-x^2 + 4x - 3)/(x - 1)

    Factor the numerator.

    The numerator becomes

    -x^2 + 3x + x - 3.

    We divide the numerator's polynomial into two groups:

    (-x^2 + 3x) is group a.

    (x - 3) is group b.

    We factor group a. We cannot factor group b because it is already in lowest term.

    So, (-x^2 + 3x) becomes

    -x(x - 3)(x - 3)

    We now this fraction:

    [-x(x-3)(x-3)]/(x - 1) = final answer.

    You can also write the final answer this way:

    [-x(x - 3)^2]/(x - 1)

    Done!

    1. 👍
    2. 👎
  3. Yes, Reiny answer's is correct.

    I went back to redo the question and got the same answer as Reiny.

    Sorry for the mistake.

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

  2. math

    a)simplify the expression and explain each step 4(3x+2)-2 b)Factor the expression below 20b-16 help please

  3. chemistry

    N2 + 3H2 --> 2NH3 how many grams of hydrogen are needed to react with 50 grams of nitrogen? Three moles of H2 per one mole of N2. How many moles of N2 is 50 grams? 1.79 moles is 50 grams. You do these problems in steps. Step 1.

  4. Algebra

    Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A- step 4 B- step 1 C- step 2 D-

  1. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

  2. math

    Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

  3. chemistry

    How would I go about doing this question, can someone explain it step by step please, my answer I keep getting is 1.17m CaCl2, but the answer is 1.35m CaCl2? A 1.30M solution of CaCl2 in water has a density of 1.1g/mL/ What is the

  4. chemistry, polar or nonpolar

    Why is NO3 nonpolar but CIF3 is polar? I looked at the lewis structures, they look similar, but why is one opposite. also, when something is polar or non polar, my teacher said I should see which atom is more electronegativity is

  1. math

    10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

  2. Math

    Davide wants to find the zeros of the polynomial p(x)=x3−2x2−9x+18. His work is shown below. Step 1: p(x)=(x+3)(x−3)(x−2) Step 2: x+3=0 x−3=0 x−2=0 Step 3: x=2, x=3, x=−3 Explain why Davide’s work shows that 2, 3,

  3. math

    When simplifying a rational fraction, why do you need to factor the numerator and the denominator? Include two examples! to get like terms Can you explain a little more? When you factor then you can cancel like terms Example: 12/3

  4. algebra 2..again

    2y^3-10y^2+12y...need to factor again..i got to the second step... 2y(y^2-5y+6)...think that's right but i don't get how to factor that out..help plz..

You can view more similar questions or ask a new question.